1 Long-term Testosterone Therapy Improves Erectile Function and Reduces Mortality in Men with Hypogonadism and Type 2 Diabetes – Updated Results from a Registry Study. Issue 1 (1st April 2022) - Saad, F; Haider, A; Haider, KS; Doros, G; Traish, A
ABSTRACT: Introduction: Erectile dysfunction affects nearly two-thirds of all men with type 2 diabetes mellitus (T2DM), in whom it is approximately 3.5 times more prevalent, has greater severity, and is less responsive to phosphodiesterase-5 (PDE5) inhibitors than in men without diabetes (Fonseca et al. Diabetologia 2004;47:1914–1923). Long-term testosterone therapy (TTh) resulted in improved erectile function in men with hypogonadism and T2DM (Diabetes Obes Metab. 2020;22:2055–2068). Objective: to investigate effects of long-term TTh for up to 12 years on erectile function and mortality in men with hypogonadism and T2DM in comparison to an untreated control group. Methods: In a registry study in men with hypogonadism (defined by total testosterone ≤350 ng/mL and at least moderate symptoms assessed by the Aging Males' Symptoms scale) in a single urology office, 361 men had T2DM. 183 men received testosterone undecanoate (TU) injections 1000 mg/12 weeks following an initial 6-week interval (T-group), 178 opted against TTh and served as controls (CTRL). IIEF-EF (5+1 questions, maximum score: 30), was assessed at each visit, and mortality recorded based on reports from the patients' general practitioners. Changes over time between groups were compared by a mixed effects model for repeated measures with a random effect for intercept and fixed effects for time, group and their interaction and adjusted for age, weight, waist circumference, blood pressure, fasting glucose, lipids and quality of life to account for baseline differences between groups. Results: Mean (median) follow-up: T-group 8.2±3.2 (8), CTRL 9.2±2.8 (10) years, total observation time: T-group 1508, CTRL 1641 years. Baseline age was 60.7±5.5 (T-group) and 63.0±4.9 years (CTRL) (p<0.0001). At baseline, PDE5-Inhibitors were used by 27.3% (T-group) and 34.3% (CTRL) (p=0.1527). ED was reported at first visit by 64.5% in the T-group and by 54.5% in CTRL. In patients not reporting ED, ED was diagnosed by use of the IIEF-EF in 30.6% and 44.4%, respectively. 4.9% in the T-group and 1.1% in CTRL had no ED (p<0.01 for all). Erectile function: In the T-group, IIEF-EF increased by 12.1±0.4 (least squares means ± standard errors) in year 12. In CTRL, IIEF-EF decreased by 14.2±0.4. The estimated adjusted difference between groups was 26.3 (95% CI: 25.1;27.5) (p<0.0001 for all). Mortality: During the entire observation period, 15 patients (8.2%) died in the T-group and 61 patients (34.3%) in CTRL (p<0.0001). Adherence to TTh was 100 per cent as all injections were administered in the office and documented. Conclusions: Long-term testosterone therapy in men with hypogonadism and T2DM improved erectile function and reduced mortality. In the untreated control group, erectile function deteriorated. Our mortality data confirm the results by Hackett et al., BJU Int 2019;123:519–529 who observed the lowest mortality in a subgroup of men receiving continuous long-term TTh. Disclosure: Yes, this is sponsored by industry/sponsor: Bayer Clarification: Industry funding only - investigator initiated and executed study Any of the authors act as a consultant, employee or shareholder of an industry for: Bayer